2016
DOI: 10.1038/laban.1117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light level, CO2 flow rate, and anesthesia on the stress response of mice during CO2 euthanasia

Abstract: Euthanasia protocols are designed to mitigate the stress experienced by animals, and an environment that induces minimal stress helps achieve that goal. A protocol that is efficient and practical in a typical animal research facility is also important. Light intensity, isoflurane, and CO2 flow rate were studied for their impact on the stress response of mice during CO2 euthanasia. Behavior was observed and scored during euthanasia and serum corticosterone was measured immediately after death. Unsurprisingly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Tumor onset was considered to have occurred when the tumor diameter reached 5 mm. On day 21, all mice were sacrificed with 30%/min carbon dioxide for ~180 sec prior to cervical dislocation (31,32) and were confirmed dead based on cardiac arrest and respiratory arrest 40-60 sec later. Tumors, lymph nodes and spleens were collected, tumors were weighed and tumor volumes were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor onset was considered to have occurred when the tumor diameter reached 5 mm. On day 21, all mice were sacrificed with 30%/min carbon dioxide for ~180 sec prior to cervical dislocation (31,32) and were confirmed dead based on cardiac arrest and respiratory arrest 40-60 sec later. Tumors, lymph nodes and spleens were collected, tumors were weighed and tumor volumes were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 108 full text articles reviewed, 71 articles were excluded as they did not meet eligibility criteria and 37 articles were included. In total, 15 papers were reviewed for mice (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), 21 papers for rats (16,22,23,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), and 5 papers were reviewed for neonatal rodents (21,(49)(50)(51)(52), with three studies reporting results for both adult mice and rats (16,22,23) and one study reporting results for both adult female mice and their pups (21,(49)(50)(51)…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Some studies evaluated different VDRs or FRs of CO 2 , some compared one or more VDR/FR of CO 2 with one or more inert or inhalant anesthetic gas and some studies compared one or more VDR/FR/percentage of CO 2 with other physical or chemical methods of euthanasia, including pentobarbital sodium, potassium chloride, cervical dislocation, and decapitation. One study evaluated the effects of different VDRs of CO 2 with or without premedication with acepromazine or midazolam (30) and one study evaluated the effects of different flow rates of CO 2 when given with differing ambient light intensities (28). Flow or volume displacement rates of carbon dioxide evaluated ranged from 0.2 L/min to 15-100%.…”
Section: Effects Of Carbon Dioxide Inhalation On Adult Micementioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that while fast displacement of 100% CO 2 decreases the duration of the stress to mice, slow displacement of CO 2 prolongs the time period of experiencing distress, ataxia, stress on breathing (Creamer-Hente et al, 2018), and decreases the duration of dyspnea (Moody, Chua, & Weary, 2014). To this end, a recent study found that a darkened chamber with slow displacement of CO 2 may alleviate some of the stress during CO 2 euthanasia (Powell, Ethun, & Taylor, 2016).…”
mentioning
confidence: 99%